HIGH FREQUENCY FILTERING OF 24-HOUR HEART RATE DATA - Stankus, Albinas; Stankus, Vytautas; Didziokas, Rimantas; Varoneckas, Giedrius (European Scientific Journal, ESJ, 2013)
Heart rate (HR) and its variability (HRV) analysis based on spectral methods have been widely applied for assessment of autonomic nervous system activities. However, an observation of existing frequency dynamic in particular spectral bands of HRV, especially when analysis is done in short time RR interval series, is problematic using these methods. We used self-developed digital filters to solve this problem. The high-frequency (HF; 0.15-0.4 Hz) band of RR intervals is filtered with 3 finite (FIR) and 4 infinite impulse response (IIR) filters from original 24-hour HR record. We showed that the use of various filters for identification of respiration influence on HR. An analysis using FIR filters gives more accurate results, but requires more calculation resources. No differences between results obtained using filtering and spectral analysis were observed. The use of FIR and IIR filters are simple and effective for processing of both, 24-hour data and short-time series of RR intervals.